The effect of femtosecond laser-assisted in situ keratomileusis on contrast sensitivity - Pinqing Yue; Xiang Wang; Zeng Wang; Ying Li; Di Wu; Hua Zhang; Pan Zhang (Frontiers in Neuroscience, 2024)
The benefits of femtosecond laser-assisted in situ keratomileusis (FS-LASIK) for correcting vision, particularly in terms of spherical equivalent (SE) and visual acuity (VA), have gained broad recognition. Nevertheless, it has remained uncertain whether FS-LASIK has a positive impact on contrast sensitivity (CS). In this study, we measured CS on seven participants by the quick contrast sensitivity function (qCSF) and compared CS before and after the surgery at two time points (1 day and 7 days after) by the repeated measures analysis of variance (ANOVA). Then, we clarified the underlying mechanisms using the perceptual template model (PTM). Furthermore, we investigated the relationship among SE, VA, and CS employing the Pearson correlation test. We found that (1) CS exhibited significant improvements on postoperative day 1, with further enhancements observed up to postoperative day 7, (2) CS improvements were dependent on spatial frequency (SF) and external noise, (3) CS improvements were attributed to the reduction of internal noise and the enhancement of the perceptual template, (4) VA and SE demonstrated significant improvement post-surgery, and (5) no significant correlations were observed among SE, VA, and CS, possibly due to limitations in sample size and lighting conditions. These findings contribute to our comprehension of FS-LASIK and provide a great indicator for assessing the outcomes of visual surgery.